Automation System For Honey Production - Saat, Shahrizal (UTeM, 2019)
The company running business of producing honey in bottle. Before this project execute, all process related to production run using manual method. Company looking for solution that could help to increase daily production rate with best quality of end product. This project solve problem facing by industries with promoted an automation system for all process related to production process. This system fully control by Programmable Logic Controller (PLC).